Table of Content - - (Journal of Arabic Language Sciences and Literature, 2025)
:Table of Content • A thematic and artistic comparison between the poems "Sunset Garden" and "Fever" by Ghazi Al-Gosaibi Dr. Khalid Saleh Alshedookhi • Literary Taste Between Al-Qadi Al-Jurjani and Abdul-Qahir Al-Jurjani: A Comparative Study Mr. Mūsā Hādī Al-Fayfī • The sufficiency of contrastive interpretation in the novel: "As If It Were a Canopy" by Moroccan Author Suad Al-Nasser, as a model Dr. Sanae Harboul • The Aesthetics of the Arabic Language in Expressing Human Relationships: A Rhetorical-Analytical Study Between Tradition and Contemporary Contexts Mr. Fahad Nawaf Alotaibi • The Point of View in the Saudi Novel Between the Narrator and the Author: Selected Models Ms. Aliah Radatallah Al-Mozainy • Linguistic Roots of Surah At-Tariq: Structure and Morphological Significance Dr. Rana Abdel-Aziz Al-Gharawi